Noninvolvement of the spore cortex in acquisition of low-molecular-weight basic proteins and UV light resistance during Bacillus sphaericus sporulation. - Setlow, B (1982)
Two major low-molecular weight, acid-soluble proteins (termed A and B proteins) were purified from Bacillus sphaericus spores and had properties similar to those of the analogous proteins from spores of other Bacillus species. These proteins were accumulated late in sporulation, when the developing spores became resistant to UV light, and were degraded during spore germination by a spore protease. A mutant of B. sphaericus unable to make spore cortex because of a block in diaminopimelic acid (DAP) biosynthesis accumulated and maintained levels of the A and B proteins similar to those in the DAP+ parent or the DAP- strain in which cortex formation was restored by growth with DAP. In addition, the DAP- strain grown without DAP acquired a level of UV light resistance identical to that of wild-type spores and at the time of appearance of the A and B proteins. These findings indicate that formation of little, if any, spore cortex is required for acquisition of UV light resistance or maintenance of high levels of A and B proteins. The data provide further support for a role of the A and B proteins in the spore's UV light resistance.